2015
DOI: 10.3232/sjss.2015.v5.n2.05
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in pastureland soils situated in A Pastoriza (NW Spain) treated with cattle slurry and NPK fertilizers

Abstract: In Galicia (NW Spain), pasturelands cover a broad extension and are mainly used to feed cattle. Farms are managed in an intensive manner, using cattle slurry and inorganic fertilizers to increase pasture production, but also increasing risks of heavy metal pollution. In this work we studied the influence of fertilization practices on total concentrations and in-depth distribution of heavy metals and related elements (As, Cd, Cr, Cu, Mn, Ni, Pb and Zn) in two forest soils (SN1, SN2) and five pastureland soils (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
3
4
2
Order By: Relevance
“…In the case of manganese, 39% of the samples analysed, mainly in the surface soil, had a pseudo-total concentration higher than the GRL. The values were higher than those reported by Seco-Reigosa et al (2015) for pasture and forest soils of the same area and similar to those reported by Caridad-Cancela et al (2002) for natural soils in Galicia. Moreover, the maximum allowable concentration range for Mn (1,500-3,000 mg kg −1 , according to Kabata-Pendias and Szteke ( 2015)) was never exceeded.…”
Section: Pseudo-total Metal Concentrations and Pollution Indicessupporting
confidence: 83%
See 3 more Smart Citations
“…In the case of manganese, 39% of the samples analysed, mainly in the surface soil, had a pseudo-total concentration higher than the GRL. The values were higher than those reported by Seco-Reigosa et al (2015) for pasture and forest soils of the same area and similar to those reported by Caridad-Cancela et al (2002) for natural soils in Galicia. Moreover, the maximum allowable concentration range for Mn (1,500-3,000 mg kg −1 , according to Kabata-Pendias and Szteke ( 2015)) was never exceeded.…”
Section: Pseudo-total Metal Concentrations and Pollution Indicessupporting
confidence: 83%
“…Thus, iron will be considered mainly in its micronutrient condition. The concentrations were higher than the total concentrations, determined by X-ray fluorescence, reported by Seco-Reigosa et al (2015) for four pasture soils of the same area. In the case of manganese, 39% of the samples analysed, mainly in the surface soil, had a pseudo-total concentration higher than the GRL.…”
Section: Pseudo-total Metal Concentrations and Pollution Indicescontrasting
confidence: 68%
See 2 more Smart Citations
“…As exposed previously for other European regions, this legislative spectrum often results confusing for farmers (Ortolano et al 2009) and in the common thought that fertilization strongly correlates with the crop yield, organic and inorganic fertilization is carried out following their own criteria. In Galicia, annual doses of 40 m3 ha −1 of poultry manure were addressed by Conde-Cid et al (2018) in agriculture areas, 100 m3 ha −1 for cattle slurry and 1000 kg ha −1 for mineral fertilizer NPK 8:24:16 were reported in pasturelands (Seco-Reigosa et al 2015), and over 200 kg N ha-1 and 50 kg P kg ha −1 for grasslands (Paz-Ferreiro et al 2010). On the other hand, the addition of organic materials different from manures on Galician soils was widely studied by different authors (Santalla et al 2011;Paz-Ferreiro et al 2012;Pousada-Ferradás et al 2011) before and after the appearance of Decree 125/2012 that regulates the usage of organic wastes in Galicia.…”
Section: Introductionmentioning
confidence: 99%